Case Report: Why Sleep and Dream Related Psychological Treatments, Such as Sleepcoaching (According to Holzinger&Klösch) and CBT-I Should Be Implemented in Treatment Concepts in the Public Health System—Description of the Nightmare Treatment Process in the Context of PTSD - Holzinger, Brigitte; Nierwetberg, Franziska; Klösch, Gerhard (Frontiers in Psychology, 2021)
In this case report we tell the story of a women diagnosed with severe PTSD, suffering from recurrent nightmares involving the traumatizing event. She participated in a 6 week lucid dreaming training, to help her reduce her nightmare frequency. Our descriptions include her dream reports as well as the results of the psychological assessment conducted. In only 6 weeks she was able to begin to change her dream plots and to improve several of the psychological measures. By this case we want to argument, that paying more attention to sleep and especially nightmares, not only in PTSD patients, should be standard in treatment processes for psychological disorders. We therefore underpin our case with literature that explains benefits of treatments specifically for sleep problems, that do not involve medication.